Self-collection of genital human papillomavirus specimens in heterosexual men. Issue 3 (9th December 2008) - Ogilvie, G S; Taylor, D L; Achen, M; Cook, D; Krajden, M
Abstract : Background: We assessed the accuracy of self-collected human papillomavirus (HPV) specimens in men compared with clinician-collected specimens from men in British Columbia and determined the prevalence of HPV subtypes at different male genital sites. Methods: Heterosexual men were recruited at the Provincial Sexually Transmitted Infection (STI) Clinic in Vancouver, Canada. Participants were randomly assigned to conduct self-collection or clinician-collected specimens first. Clinicians obtained specimens using emery paper followed by saline-moistened Dacron swab from three genitourinary sites: glans penis/foreskin, penile shaft (ventral and dorsal surfaces) and scrotum. Participants received written instructions and took specimens from one of the three sites using the same technique as clinicians. HPV testing was performed with the Roche Amplicor HPV test and samples found to be reactive were tested with the Roche Linear Array HPV typing assay to establish the HPV genotype(s) in the sample. Results: Overall prevalence of any HPV genotype from any site was 69.8% in clinician-collected specimens and 55.3% in self-collected specimens. Order of collection (clinician vs self-collected) did not impact on the prevalence of HPV in the specimens. The κ scores for agreement between clinician-collected and self-collected specimens ranged from fair to excellent. Overall, there was better agreement between self-collected and clinician-collected specimens for HPV-18 (range: κ = 0.88 to 0.92) than for HPV-16 (range: κ = 036 to 0.62). Conclusion: HPV is a prevalent genital tract infection in men. Site-specific agreement for specific HPV genotypes between clinician-collected and self-collected specimens varied broadly and neither clinicians nor patients routinely obtained samples with consistently higher or lower prevalence at specific genital sites, indicating there are continued opportunities to improve techniques for clinician-collected and self-collected male specimens for HPV.